SPECIAL PHYSICAL FITNESS DYNAMICS OF 15-16-YEAR-OLD TAEKWONDO WTF BOYS ARE IN TRAINING GROUP - Nozimov Holmurod Qobilboyevich. (Research Focus International Scientific Journal, 2023)
On the basis of pedagogical experience, the efficiency of specific exercises targeted at the development of special physical training and technical-tactical training of 15-16-year-old taekwondo players enrolled in specialist sports schools was investigated in this research.